Concerning the preparation of 6-bromotryptamine. (9th April 2021) - Scott Wiens, P.; Johnson, Jerry L.; Gribble, Gordon W.
Abstract: Most of the previous syntheses of the marine natural product 6-bromotryptamine have almost certainly led to partial debromination resulting in an impure product containing tryptamine. We show that loss of bromine occurs when lithium aluminum hydride is employed as a reducing agent in the final reaction step leading to 6-bromotryptamine. Reductive-debromination is also likely to intrude during some of the syntheses of 6-bromoindole, the typical precursor to 6-bromotryptamine. None of the seven described syntheses of 6-bromotryptamine that involve a reduction sequence from 6-bromoindole have reported elemental analyses as a measure of purity. Graphical abstract: Image 1 Highlights: The synthesis of 6-bromoindole is conveniently achieved from 4-bromo-2-nitrotoluene. The pivotal marine natural product 6-bromotryptamine is synthesized from 6-bromo-3-(2-nitrovinyl)indole. The choice of reducing agents is critical to avoid reductive debromination of the 6-bromotryptamine product Elemental analysis for bromine content is essential to establish the purity of the 6-bromotryptamine.